2008
DOI: 10.1016/j.cbpb.2008.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of peroxisome proliferator-activated receptors (PPARs) and their gene expression in the differentiating adipocytes of red sea bream Pagrus major

Abstract: To investigate the molecular mechanism of fish adipocyte differentiation, the three subtypes of PPAR genes (alpha, beta and gamma) were characterized in a marine teleost red sea bream (Pagrus major). The primary structures of red sea bream PPARs exhibited high degrees of similarities to their mammalian counterparts, and their gene expression was detected in various tissues including adipose tissue, heart and hepatopancreas. During the differentiation of primary cultured red sea bream adipocytes, three PPARs sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 37 publications
4
44
2
Order By: Relevance
“…Studies in mammals have indicated that PPAR a is involved in the early phase of adipocyte differentiation [32]. In fish, PPAR a showed a transient increase during the induction period [11]. In this result, the level of PPAR a showed a transient increase after inducing for 1 day, which agrees with findings in mammals and other fish [11,32] (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Studies in mammals have indicated that PPAR a is involved in the early phase of adipocyte differentiation [32]. In fish, PPAR a showed a transient increase during the induction period [11]. In this result, the level of PPAR a showed a transient increase after inducing for 1 day, which agrees with findings in mammals and other fish [11,32] (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that FAS and SCD are all induced during differentiation in 3T3-L1 adipocyte [40,41]. In red sea bream, FAS and SCD were only induced in the later stage of differentiation [11]. In Atlantic salmon, however, the level of SCD was highest from the middle stage to the later stage [17].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…4A-C ). Previous in vitro analysis in other teleost species (i.e., Pagrus major ) revealed that pparg is expressed in cultured preadipocytes as well as adipocytes ( 34 ). Although we are unable to exclude the possibility that zebrafi sh preadipocytes express pparg below our applied level of detection, zebrafi sh pparg appears to be robustly expressed only in mature adipocytes after the onset of neutral lipid deposition.…”
Section: Markers Of the Zebrafi Sh Adipocyte Lineagecontrasting
confidence: 62%
“…Three subtypes of PPARs, termed a, b (d), and c, have been identified in mammals' liver as well as in fish. The overall features including the primary structure and tissue distribution are similar to those of their mammalian counterparts, 34,35 resulting a good tool in fish metabolism studies. Concerning SREBP, this sterol-sensitive transcription factor is synthesized as a membrane-bound precursor protein that in the liver is cleaved to its mature form when cellular sterols are depleted.…”
Section: Introductionmentioning
confidence: 75%